L’Avversario. Il romanzo di Carrère nella lettura scenica di Invisibile Kollettivo (Itinera, 2019)
The paper aims to illustrate the Italian play L’Avversario, a work by Invisibile Kollettivo that tries to translate into a theatrical show the roman written by the French author Emmanuel Carrère.Both in the roman and in the play the most important aspect is the author’s point of view together with his feelings. This results quite normal referring to a book, but it is way too original in a theatrical play. So, the paper tries to explain the motivation that moved the Italian artists to stay loyal to the spirit of the book, choosing the form of the scenic reading for bringing it on stage. Theatre, Carrère, Lettura scenica, Teatro dell’Elfo, Invisibile Kollettivo